BILATERAL PLEURAL EFFUSION IN PARAGONIMIASIS A CASE REPORT - Jaturat KANPITTAYA, Jaturat KANPITTAY; TEERATAKULPISARN, Jamaree; KUPTARNOND, Chusak; KUPTARNOND, Chusak; TESANA, Smarn; MAIRIANG, Eimorn (The ASEAN Journal of Radiology, 2023)
A 14-year-old boy was admitted with chest pain, low grade fever and a productive cough for about 2 months. The chest film showed bilateral pleural effusion. The Significant laboratory finding was eosinophilia, 22% in peripheral blood and 49% in pleural fluid. The images of ultrasonogram and computed tomography revealed unexplained exudative bilateral pleural effusion, bizarre appearance and a questionable moving organism. Finally the operation was done and a living parasite of Paragonimus heterotremus was found.